Effects of a behaviour management technique for nursing staff on behavioural problems after acquired brain injury. Issue 4 (21st April 2019) - Winkens, Ieke; van Heugten, Caroline; Pouwels, Climmy; Schrijnemaekers, Anne-Claire; Botteram, Resi; Ponds, Rudolf
ABSTRACT: The ABC method is a behaviour management technique for use by nurses. ABC refers to the identification of Antecedent events, target Behaviours, and Consequent events. In this longitudinal intervention study with double baseline measurements we evaluated the effectiveness of the ABC method in patients with behavioural problems after acquired brain injury. Fifty-six patients participated in this study. Outcome was measured in terms of overall neuropsychiatric problem behaviour, aggression, apathy and emotional burden experienced by nurses. A process evaluation was performed to investigate usability and acceptability of the method and identify factors that influenced effectiveness. Friedman's ANOVA showed a small significant reduction over time in overall neuropsychiatric problem behaviour and aggression. The reduction was most prominent between the first baseline measurement and the post-implementation and follow-up measurements, not between the second baseline measurement and the post-implementation or follow-up measurements. This first group study on the effects of the ABC method could not prove this technique is effective for patients with behavioural problems after acquired brain injury. Nurses indicated that the ABC method was not fully implemented in their daily routines. This may have influenced results and makes it yet premature to draw firm conclusions on the effects of the ABC method.